Orientasi Karyawan Pembentukan Employee Experience di Perusahaan Petrokimia - Arianto Ariandi; Nugroho BS. Sukamdani; Maya Dewi Dyah Maharani (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Petrochemical company faces talent competition. Employee Experience (EX) is a new concept that is more profitable and builds Engagement. Research applies orientation as an area of HR management to apply EX. The data obtained through a descriptive approach and associative analysis with analytical tools with the results of orientation preparation, first day of work, first week activities, feedback and evaluation and evaluation of orientation activities have a positive and significant effect on Employee Experience only on the first month's feedback which has no effect positive and significant.